On Strong, Resolute Labor Union Leaders. (21st May 2015) - Caya, Sinan
Abstract: Unions were initially created as economic supports for workers. Along the course of time, they developed with difficulties and acquired social and invariably political dimensions. Unions' emergence in Turkey was late, while their improvement was painful. All over the world, as unions grew bigger, union activities got more professional along with acquirement of new technical possibilities, on one hand; and considerable losses in the early enthusiasm also occurred, on the other hand. Business owners sometimes associated unions with radical opposing political currents in their inappropriate fear. But the mentioned currents did try to penetrate into those establishments, where economical considerations with a view to welfare were supposed to have been the overweighing Issues. Even though at times, some union leaders themselves essentially neglected the workers while solely focusing on an increase of their own might, through false unions; their wrongdoing should not be loaded on to honest union activities. In this article, also a novel by Robbins which isvery related to the topic, is made much use of.